Stand-alone surgery for mild to moderate glaucoma and ocular surface disease: June consultation #1. Issue 6 (June 2020) - Unknown
Abstract : An elderly pseudophakic man with mild to moderate glaucoma was marginally controlled with four medications that were exacerbating his ocular surface disease. Our experts describe their preferred management for stand-alone glaucoma surgery for this patient. Abstract : A generally healthy and independent 83-year-old man presented with long-standing, mild to moderate glaucoma. He had uneventful cataract surgery several years earlier. He also had previous selective laser trabeculoplasty (SLT) with only slight reduction in his intraocular pressure (IOP). His untreated IOP was middle to upper twenties. His recent IOP has been running in the middle to upper teens while using 4 medications in each eye: brimonidine, dorzolamide, latanoprost, and netarsudil. His general health is good, and he is not taking any anticoagulants. He reports no trouble administering eyedrops, 1 drop or 2 drops each day, but finds his current eyedrop schedule unmanageable, and his eyes are always red. He was essentially emmetropic, but he had been considerably myopic before his cataract surgery; his axial length is 27.31 mm in the right eye and 27.18 in the left eye (Figure 1 ). Sequential visual fields are shown in Figure 2 . His nerve fiber layer optical coherence tomography image is shown in Figure 3 . His angles are wide open in each eye and his IOL is well positioned with a clear and intact posterior capsule. His conjunctiva and sclera are moderately injected but healthy and without scarring. He was referred for surgical intervention to reduce the complexity of his eyedrops regimen and improve the condition of his ocular surface. He does not want a repeat SLT procedure because it "did not work the first time." Which stand-alone glaucoma procedure would you recommend for each eye?